A new genus and species of mud snake from Myanmar (Reptilia, Squamata, Homalopsidae) - Köhler, Gunther; Khaing, Khin Pa Pa; Than, Ni Lar; Baranski, Damian; Schell, Tilman; Greve, Carola; Janke, Axel; Pauls, Steffen U. (Zootaxa, 2021)
Based on two male and two female individuals, we describe a new genus and species of mud snake, Myanophis thanlyinensis gen. nov., sp. nov., from the vicinity of the campus of East Yangon University, Yangon, Thanlyin, Myanmar. This species differs from every other homalopsid species by the following combination of characters: (1) dorsal scales smooth, row formula 21–21–19 or 21–21–17; (2) tail short, ratio tail length/SVL 0.185–0.204 in males, 0.160–0.167 in females; (3) nasal scales separated; (4) 125–126 ventral scales in males, 120–122 in females; (5) 38–39 subcaudal scales in males, 32–34 in females; and (6) hemipenis bilobed. Its matrilineal genealogy (based on analyses of 16S and cytochrome b sequences), associates Myanophis thanlyinensis gen. nov., sp. nov. most closely with species of the genera Myrrophis and Gyiophis. The new taxon differs from the species of Myrrophis and Gyiophis by having a bilobed hemipenis (vs. unilobed). Myanophis thanlyinensis gen. nov., sp. nov. differs further from the species of Myrrophis by having 125–126 ventral scales in males and 120–122 in females (vs. 137–162 and 137–164, respectively), and 38–39 subcaudal scales in males and 32–34 in females (vs. 39–55 and 37–52, respectively). Myanophis thanlyinensis gen. nov., sp. nov. differs further from the species of Gyiophis by lacking dark blotches along flank (vs. present), and by having 21 dorsal scales rows at midbody (vs. 25). We provide an identification key to the homalopsid species known to occur in Myanmar. As a novelty to the classic holotype description and characterization, the individual has been genome sequenced by Illumina short-read technology and its genome has been assembled into a draft nuclear genome and a complete, annotated mitochondrial genome. This innovative approach comprehensively and permanently characterizes the genomic variation of the holotype.